A Tale of Two Levels: Analyzing the Discoverability and Impact of Item-Level Description in EAD Finding Aids. Issue 3 (2nd October 2021) - Daybell, Paul; Payant, Andrea; Woolcott, Elizabeth; Skeen, Becky; Arnljots, Anna-Marie; Meyer, Kurt
Abstract: Utah State University Libraries Cataloging and Metadata Services unit investigated the discoverability of local EAD finding aids. Two versions of the same finding aid were described at the file level and item level, respectively. Analytics for each guide were assessed to discover which descriptive level was most frequently accessed. Patron search terms and finding aid tags was also assessed. Data shows that personal names are the most common type of search term, search terms are most commonly found in the Collection Inventory, and that the availability of item-level description improves discovery by an average of 6100% over file-level descriptions.